Vírgulas em esquema simples: usos em textos narrativos - Francisco, Isabela [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The aim of this paper is to describe and analyze the conventional and unconventional uses of commas in a simple scheme in narrative texts written by students in the first and last years of Elementary School II (EF II) in a public school in the interior of São Paulo. By means of a quantitative survey of syntactic structures in which commas are or should have been used, we investigate whether the use of commas in narrative texts, in addition to guiding the functioning of the syntactic structure, can signal the delimitation of prosodic boundaries, typical of spoken utterances. The purpose of this study is justified by the complexity of using this punctuation mark, given the lack of consensus among grammarians on the rules of its use, on the one hand, and by the fact that it provides different interpretations on the establishment of the relationship between speech and writing. We take a view that sees the relationship between speech and writing in a more complex way than that which takes these linguistic modalities on the basis of their phonic and graphic materiality, respectively. We adopt the view that speech and writing are modes of enunciation that are constituted by oral and literate practices. In view of this complexity, we investigated the presence and absence of commas in a semi-longitudinal sample of texts written by secondary school students. This research assumes the hypothesis that the use of commas in a simple scheme in narrative texts signals prosodic aspects of spoken utterances, i.e. that E2 students use commas not only syntactically, but also to represent characteristics of spoken utterances. Based on the results obtained, there is evidence that the conventional use of commas increases in the final stage of secondary education (9th grade) and so do the functions of their use. In relation to the hypothesis, evidence was found that the prosodic organization of utterances is related to the use of commas in simple schemes. The length of certain structures, together with the possibility of the semantic-pragmatic functions of the comma coinciding with prosodic boundaries, motivates the use (conventional or unconventional) of the punctuation mark in question.

The aim of this paper is to describe and analyze the conventional and unconventional uses of commas in a simple scheme in narrative texts written by students in the first and last years of Elementary School II (EF II) in a public school in the interior of São Paulo. By means of a quantitative survey of syntactic structures in which commas are or should have been used, we investigate whether the use of commas in narrative texts, in addition to guiding the functioning of the syntactic structure, can signal the delimitation of prosodic boundaries, typical of spoken utterances. The purpose of this study is justified by the complexity of using this punctuation mark, given the lack of consensus among grammarians on the rules of its use, on the one hand, and by the fact that it provides different interpretations on the establishment of the relationship between speech and writing. We take a view that sees the relationship between speech and writing in a more complex way than that which takes these linguistic modalities on the basis of their phonic and graphic materiality, respectively. We adopt the view that speech and writing are modes of enunciation that are constituted by oral and literate practices. In view of this complexity, we investigated the presence and absence of commas in a semi-longitudinal sample of texts written by secondary school students. This research assumes the hypothesis that the use of commas in a simple scheme in narrative texts signals prosodic aspects of spoken utterances, i.e. that E2 students use commas not only syntactically, but also to represent characteristics of spoken utterances. Based on the results obtained, there is evidence that the conventional use of commas increases in the final stage of secondary education (9th grade) and so do the functions of their use. In relation to the hypothesis, evidence was found that the prosodic organization of utterances is related to the use of commas in simple schemes. The length of certain structures, together with the possibility of the semantic-pragmatic functions of the comma coinciding with prosodic boundaries, motivates the use (conventional or unconventional) of the punctuation mark in question.
Commas in simple outline: uses in narrative texts
Keywords: Vírgula; Língua portuguesa; Linguística; Ensino fundamental II; Comma; Portuguese language; Linguistics; Elementary school II